Hydraulic Design of Way Kandis River Embankment (Case Studies at the Lampung State Polytechnic River Section) - Bagas Arya Hermuda; Gunawan Manihuruk; Realis Prasetyawan; Didik Kuswadi (Jurusan Teknologi Pertanian, 2014)
Flooding is a condition where there is overload of water in the channel or inhibition of water flow to the drainage channel, so the overflow of water inundated the surround area. Embankment is defined as a waterwork which it was used to reduced or prevented the overtoping of water. The purpose of this study were (1) determine the plan flooding discharge of Way Kandis river, (2) made the hydraulic design of Way Kandis River embankment segment Polinela. Steps of research activities were the preparation, survey and topographical measurements, collected hydrological data, processed of topography and hydrology data, counted the design maximum discharge, design of embankment river. The results showed that (1) the design discharge of return period 25 years was 29.13 m³/s, (2) the result of hydraulic design of Way Kandis River embankment at the POLINELA segment were the design channel capacity by 30.18 m3/s, the base width of the channel (b) by 5.1 m, the depth of flow (h) by 1.7 m, the slope embankment (1:m) by 1:2, height of freeboard by 0.5 m. Keywords: hidraulic design of embankment, plan of flooding discharge, design of channel capacity